Who pays the child penalty? Evidence from the panel study of income dynamics - Jamie M. Emery (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2022)
The impact of children on the labour market outcomes ofwomen relative to men (the "child penalty") is well-documented, yet there is a paucity of evidence on the mechanisms behind it. I use 50 years of data from the Panel Study of Income Dynamics (PSID) to explore the importance of gendered norms and preferences and present three main findings. First, there is extensive heterogeneity in the penalty across groups ofwomen, but not men, based on their race, marital status, and birth cohort. Second, there is a strong link between the penalty and individual-level gender-related beliefs. Third, women who grew up in households with a less traditional division of labour exhibit a smaller penalty when they have children. Taken together, my findings demonstrate that gender norms are a key driver of the penalty.
Keywords: 330; Lohnstruktur; Geschlechterrolle; Soziale Norm; USA